A translation-invariant renormalizable non-commutative scalar model - Gurǎu, Rǎzvan; Magnen, Jacques; Rivasseau, Vincent; Tanasa, Adrian (Communications in mathematical physics, 2009)
In this paper we propose a translation-invariant scalar model on the Moyal space. We prove that this model does not suffer from the UV/IR mixing and we establish its renormalizability to all orders in perturbation theory.